Graphene oxide hole injection layer for high-efficiency polymer light-emitting diodes by using electrophoretic deposition and electrical reduction. (November 2015) - Kim, Jungyoon; Ganorkar, Shraddha; Kim, Young-Hwan; Kim, Seong-Il
Abstract: Graphene oxide (GO) is a fascinating nanomaterial with tremendous potential for electronic devices which show high performance when the properties of GO are properly tuned like reduced graphene oxide (RGO). Here, we report a simple, cost effective and precisely controllable methods to fabricate high-quality RGO films as a hole injection layer (HIL) for high efficiency polymer light-emitting diodes (PLEDs). First, GO is electrophoretically deposited and electrically reduced to produce RGO films. The deposition and reduction of films are electrical methods; hence the thickness and the degree of reduction for GO films can be easily manipulated by controlling electrical parameters and time. The performance of PLEDs with RGO film as HIL is measured and compared with GO and (poly(3, 4-ethylenedioxythiophene)polystyrene sulfonate) (AI4083), and shows better results for luminance and current density. The optimized maximum luminance and current efficiency of the PLEDs with RGO as HIL are found to be 12830 cd/m 2 and 3.35 cd/A, respectively.